Traumatic pneumatocele in an 11-year-old boy – report of a rare case and review of the literature - Matuszczak, Ewa; Oksiuta, Marzanna; Hermanowicz, Adam; Dębek, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2017)
The authors present a case of a pneumatocele associated with blunt trauma in a child. An 11-year-old boy was admitted to the emergency department after he was knocked over and his chest was trapped under a soccer goal. Chest computed tomography (CT) revealed several cavities in the lobes of both lungs. The CT of the abdomen revealed traumatic laceration of the liver. The patient was treated conservatively. His condition was stable and subsequently improved. He was discharged 19 days later. After nine months, a chest radiograph showed complete resolution of the pneumatocele, and abdominal ultrasound demonstrated complete resolution of the liver hematoma. A traumatic pneumatocele is a benign lesion resulting from blunt chest trauma, usually in children and young adults, which typically requires only conservative treatment. The CT scanning is the most sensitive method for the detection of traumatic pneumatoceles. All emergency physicians should be familiar with the diagnosis and management of this condition, to avoid unnecessary invasive procedures.